The living house an anthropology of architecture in South-East Asia - Waterson, Roxana (Singapore Oxford University Press, 1991)
This work presents a detailed description of the centrally significant role of houses in South-East Asian social systems. Focusing on Indonesia, the book traces the historical links between architectural forms, revealing a much wider field of enquiry, closely related to the distribution of
Austronesian languages and cultures, and extending as far as Madagascar, Japan, and Oceania. A vivid picture of how people shape buildings and buildings shape people, this study provides new insights into kinship systems, gender symbolism, cosmological ideas, and life itself.
Includes bibliographical references (pages 249-258) and index.
Keywords: Dwellings -- Indonesia; Dwellings -- Southeast Asia; Vernacular architecture -- Indonesia; Vernacular architecture -- Southeast Asia; Indonesia -- Social life and customs; Southeast Asia -- Social life and customs